Effect of a high-intensity short-duration cycling elevation training mask on VO2max and anaerobic power. A randomized controlled trial - Devereux, Gavin; Le Winton, Holly G.; Black, Jane; Beato, Marco (Biology of Sport, 2022)
This study investigated the effect of high-intensity interval training (HIIT) cycling elevation training mask (ETM) in moderately trained participants on both aerobic (V̇ O2max) and anaerobic power performance. Sixteen participants, five females (25.8 ± 7.6 years) and eleven males (22.2 ± 3.5 years) took part in this randomized controlled trial. Participants were assigned to the experimental group (ETM, n = 8 participants) wearing an ETM or the control group (CON, n = 8 participants) without the ETM. V̇ O2max was determined during a standardized protocol using Cortex Metalyzer-3B on a cycle ergometer. Peak and average power were calculated a 30-second Wingate test. Participants completed 4-weeks (two sessions a week) of high-intensity cycle training. Each training session consisting of 4 separate bouts of 4-minutes of high-intensity cycling exercise. After the training period, ETM reported an increment in V̇ O2max (effect size (d) = 1.19), peak power (d = 0.77), and average power (d = 0.76). CON reported an increment only in V̇ O2max (d = 1.00). No-between group differences were found in any parameter (ANCOVA), therefore the two protocols should be considered equally effective. In conclusion, this study reported that both HIIT protocols significantly enhance V̇ O2max in a very short training period (4 weeks).